Implementation of an Image Stitching Algorithm to a Low-Cost Digital Microscope - Botan, Renan; Coco, Klaus Fabian; Komati, Karin Satie (Proceedings - Brazilian Symposium on Computer Graphics and Image Processing, 2017)
In this work we propose an implementation approach to a feature-based algorithm that stitch images which comes form MicroScanner, a low cost digital microscope created at Mogai Information Technology. This program solve the trade-off problem between field of view and resolution. These codes were developed in C++ language, with help of OpenCV library. The sequence of pictures taken is used by the program to reduce computing costs and increase reliability of the resulting mosaic. In addition, the results achieved maintain the quality from original images, and presents better quality and more effective results than previous related works.